1989
DOI: 10.1007/bf00915036
|View full text |Cite
|
Sign up to set email alerts
|

The differential validity of teacher ratings of Inattention/Overactivity and Aggression

Abstract: The ability of school-based measures of child behavior to predict differentially the IOWA Conners teacher rating scale Inattention/Overactivity (IO) and Aggression (A) factors was evaluated in a sample of 71 school-aged boys. Multiple measures and multiple methods of assessment were utilized to provide a comprehensive assessment of social and academic behavior. These included direct observations of children in the classroom and on the playground, examination of the organization of children's desks, measures of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(45 citation statements)
references
References 23 publications
3
42
0
Order By: Relevance
“…The IRS was stable over two administrations to parents and teachers, exhibited convergent validity by correlating with behavioral measures of impairment, and was highly accurate in discriminating between children diagnosed with ADHD and those without. Partial correlations suggested some convergent validity, and partial correlations were similar to those reported in similar school-age samples investigating comparable issues related to the uniqueness of assessment components (e.g., Atkins et al, 1989). The optimal cut-point in this sample was any score greater than or equal to 3.…”
supporting
confidence: 50%
See 1 more Smart Citation
“…The IRS was stable over two administrations to parents and teachers, exhibited convergent validity by correlating with behavioral measures of impairment, and was highly accurate in discriminating between children diagnosed with ADHD and those without. Partial correlations suggested some convergent validity, and partial correlations were similar to those reported in similar school-age samples investigating comparable issues related to the uniqueness of assessment components (e.g., Atkins et al, 1989). The optimal cut-point in this sample was any score greater than or equal to 3.…”
supporting
confidence: 50%
“…After passing an initial phone screen, each child and his primary caretaker attended a screening session in which the child completed intelligence and achievement testing (Wechsler, 1991). Children were diagnosed with ADHD using the primary caretaker's report on the DISC, Version 2.3 (Shaffer et al, 1996) and the teacher report on the SNAP-IV checklist (Atkins, Pelham, & Licht, 1989). Symptoms were counted as present if endorsed by the parent or teacher with overlap between at least one symptom.…”
Section: Study 2 Participantsmentioning
confidence: 99%
“…Both the inattention/overactivity (IO) and oppositional defiant (OD; sometimes referred to as aggression) factors, identified in previous research have made significant and unique contributions toward predicting observed classroom behaviors (Atkins, Pelham, & Licht, 1989). This brief measure consists of 15 items that assess difficulties with attention, overactivity, impulsivity, defiance, and moodiness.…”
Section: Measures-the Trf (Achenhachmentioning
confidence: 99%
“…ODD were less accepted and more rejected by peers than children with ADHD only or ODD only [15]. However, such finding was not supported by other studies [5,17]. For example, it was found that peer difficulties were uniquely associated with ADHD symptoms independent of aggression [17] or ODD/ conduct problems [5].…”
Section: Peer Functioningmentioning
confidence: 65%
“…However, such finding was not supported by other studies [5,17]. For example, it was found that peer difficulties were uniquely associated with ADHD symptoms independent of aggression [17] or ODD/ conduct problems [5]. Taken together, studies on peer functioning in children with ADHD or ODD alone versus children with comorbid ADHD ?…”
Section: Peer Functioningmentioning
confidence: 79%